Preparation method of electrode with high anti-pole-reversion performance for fuel cell
By electroplating elements such as Ru, Co, Mn on the carbon paper electrode of the fuel cell, the durability problem caused by the reversed pole phenomenon of the fuel cell is solved, significantly improving the anti-reverse time and reducing the cost.
Patent Information
- Application Number
- CN202411926536.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-25
AI Technical Summary
In the field of fuel cells, the durability of proton exchange membrane fuel cells is low, especially the performance degradation caused by reverse polarity phenomenon has not been effectively solved.
Through electroplating technology, Ru, Co, Mn, Cr, Nb, Mo, Ti plasmas were electroplated on carbon paper to prepare electrodes with high anti-reverse properties. The method includes applying a gradient voltage on the carbon paper and performing multiple calcinations to ensure complete reduction and stability of the catalyst.
The anti-reverse time of the fuel cell is significantly improved, the cost of the fuel cell stack is reduced, and more efficient electrochemical performance is achieved.
Smart Images

Figure CN119725573A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of fuel cells, and in particular to a method for preparing an electrode with high anti-reverse polarity performance for a fuel cell. Background Art
[0002] With the continuous development of society, the impact of fossil energy on the environment is increasing, and it is crucial to find a new energy carrier. At present, green energy represented by hydrogen energy has the characteristics of cleanliness, high efficiency, and environmental friendliness, and has a higher energy density than traditional fossil energy. In addition, at the hydrogen energy use end, hydrogen fuel cells have attracted great attention from the scientific community because their reaction product is only water. However, in the field of hydrogen fuel cells, the durability of proton exchange membrane fuel cells has always been a problem that needs to be solved urgently, among which the battery reverse polarity phenomenon is one of the important reasons for the decline in fuel cell performance.
[0003] The reverse polarity phenomenon is caused by insufficient hydrogen fuel supply at the anode when the fuel cell stack is under conditions of rapid load change, start-stop, or when the catalyst layer is flooded, which leads to an increase in the anode potential, a decrease in the single cell voltage, or even a negative value, which can cause permanent damage to the battery performance. Currently, the commercial method is mainly to increase the reverse polarity time of the fuel cell by adding a highly active OER catalyst to the Pt / C catalyst, reduce the severe carbon corrosion caused by the reverse polarity phenomenon, and reduce the agglomeration of the Pt catalyst. However, the membrane electrode prepared by this method has a short anti-reverse polarity time when assembled into a fuel cell, which does not meet the requirements of the fuel cell stack. Summary of the invention
[0004] The object of the present invention is to provide a method for preparing an electrode with high anti-reverse polarity performance for a fuel cell. The method uses electroplating technology to ionize Ru, Co, Mn, Cr, Nb, Mo, Ti and the like in a solution onto carbon paper to obtain an electrode with high anti-reverse polarity performance.
[0005] In one aspect of the present invention, the present invention provides a method for preparing an electrode with high anti-reverse polarity performance for a fuel cell. According to an embodiment of the present invention, the method comprises the following steps:
[0006] (1) stirring deionized water, non-precious metal precursor, precious metal precursor and additive to form a uniform solution;
[0007] (2) placing the cathode electrode in ethanol for ultrasonic treatment;
[0008] (3) Metal rod or metal sheet as anode electrode;
[0009] (4) Apply a gradient voltage across the electrodes for 1 to 3 cycles (plating a thin base layer);
[0010] (5) calcining the plated cathode electrode in a reducing atmosphere (to ensure that the plated catalyst is completely reduced, to improve the conductivity and stability of the electrode, and to ensure that the subsequent plating layer is more solid);
[0011] (6) then applying a gradient voltage to both ends of the electrode obtained in step (5) for 2 to 6 cycles;
[0012] (7) calcining the plated cathode electrode in a stable gas atmosphere to obtain the electrode with high anti-reverse polarity performance for the fuel cell.
[0013] In addition, the method for preparing an electrode with high anti-reverse polarity performance for a fuel cell according to the above embodiment of the present invention may also have the following additional technical features:
[0014] In some embodiments of the present invention, in step (1), the weight parts of the raw materials are as follows: 1-200 parts of deionized water, 0.1-25 parts of non-precious metal precursor, 0.1-50 parts of precious metal precursor, and 1-200 parts of additives.
[0015] In some embodiments of the present invention, in step (1), the non-precious metal precursor is one or more of CoSO4, MnSO4, NbCl5, MoCl4 or TiCl4, the precious metal precursor is RuCl3 or H2IrCl6, and the additive is K2SO4 or Na2SO4.
[0016] In some embodiments of the present invention, in step (2), the cathode electrode is one of carbon paper, titanium felt, nickel felt or titanium mesh; the size of the cathode electrode is 2×2 to 5×5 cm 2 , the ultrasonic time is 30 to 60 minutes.
[0017] In some embodiments of the present invention, in step (3), the metal rod is one of a cobalt rod, an iron rod, a nickel rod, and a copper rod, and the metal sheet is one of a cobalt sheet, an iron sheet, a nickel sheet, and a copper sheet.
[0018] In some embodiments of the present invention, in step (4), the gradient voltage is set as follows: between 1 and 3 mA·cm -2 The current density was 5-7 mA·cm -2 The current density is 10-12 mA·cm -2 The current density was 5-7 mA·cm -2 The current density is 1-3 mA·cm -2 The current density is set and run for 1 to 3 minutes.
[0019] In some embodiments of the present invention, in step (5), the reducing atmosphere is one of H2, CO or N2\H2 mixed gas; the calcination temperature is 250-500°C and the calcination time is 1-3h.
[0020] In some embodiments of the present invention, in step (6), the gradient voltage is set as follows: between 4 and 6 mA·cm -2 The current density is 8-10 mA·cm -2 The current density is 14-16 mA·cm -2 The current density is 8-10 mA·cm -2 The current density is 4-6 mA·cm -2 The current density is set and run for 1 to 5 minutes.
[0021] In some embodiments of the present invention, in step (7), the stabilizing atmosphere is one of N2, Ar or N2 / Ar mixed gas; the calcination temperature is 250-500°C, and the calcination time is 1-3h.
[0022] In another aspect of the present invention, the present invention provides an electrode with high anti-reverse polarity performance for a fuel cell prepared by the method for preparing an electrode with high anti-reverse polarity performance for a fuel cell.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] 1. The high anti-reverse electrode prepared by the present invention adopts the electroplating process, which is mature and can be mass-produced, and can greatly reduce the cost of the anti-reverse electrode of the fuel cell.
[0025] 2. The catalyst electroplated onto the carbon paper of the present invention introduces a large amount of non-precious metal elements, which reduces the amount of precious metals used and further reduces the cost of the fuel cell.
[0026] 3. The catalyst electroplated onto the carbon paper of the present invention introduces a large amount of acid-resistant elements Co, Mn, Cr, Nb, Mo, and Ti, thereby increasing the anti-reverse polarity time of the catalyst in the fuel cell. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a performance diagram of a fuel cell having an electrode with high anti-reverse polarity performance in Example 1 of the present invention;
[0028] Figure 2 This is a diagram showing the anti-reverse polarity performance of the high anti-reverse polarity electrode in Example 1 of the present invention. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] Example 1
[0031] An electroplating solution for preparing an electrode with high anti-reverse polarity performance comprises the following raw materials: 200 mg of a noble metal precursor RuCl3, 65 mg of a non-noble metal precursor CoSO4, 36 mg of a non-noble metal particle precursor MnSO4, 2 g of an additive K2SO4, and 100 ml of deionized water.
[0032] A method for preparing an electrode with high anti-reverse polarity performance for a fuel cell comprises the following steps:
[0033] (1) Pour 100 ml of deionized water into a beaker, then weigh 200 mg of RuCl3, 65 mg of CoSO4, 36 mg of MnSO4 and 2 g of K2SO4 into the beaker and stir well to form a uniform solution.
[0034] (2) Cut a 2 cm × 2 cm piece of carbon paper and place it in a beaker containing ethanol solution and ultrasonicate for 30 min.
[0035] (3) Carbon paper was used as the cathode and the anode was a cobalt rod with a length of 8 cm and a diameter of 2 mm.
[0036] (4) Then a gradient voltage is applied across the electrodes, ① at 2 mA cm -2 ② At 6 mA·cm -2 ③ At 10 mA·cm -2 ④ At 6 mA·cm -2 ⑤ At 2 mA·cm -2 current density and run for 1 min, then cycle 2 times according to ①②③④⑤.
[0037] (5) Calcine the plated electrode carbon paper at 350°C in a hydrogen atmosphere for 1 h.
[0038] (6) Then a gradient voltage is applied to both ends of the electrode obtained in step (5), ① at 6 mA cm -2 ② At 10 mA·cm -2 ③ At 15 mA·cm -2④ At 10 mA·cm -2 ⑤ At 6 mA·cm -2 current density and run for 2min, then cycle 6 times according to ①②③④⑤.
[0039] (7) The plated electrode carbon paper is calcined at 350° C. for 1 h in a nitrogen atmosphere to obtain an electrode with high anti-reverse polarity performance for a fuel cell, that is, carbon paper with electroplated RuCoMn catalyst.
[0040] Test method for fuel cell anti-reverse polarity: Weigh 100 mg of Pt / C to make a slurry as the cathode and anode catalyst of the fuel cell, and the anode equivalent is 0.1 mg / cm 2 , cathode equivalent is 0.3mg / cm 2 Then, the anode is an electrode plated with RuCoMn catalyst (i.e., the electrode with high anti-reverse polarity performance for fuel cells prepared in step (7)), and the cathode is carbon paper without catalyst plating, and then a membrane electrode is prepared.
[0041] When testing the performance, pure hydrogen is introduced into the anode side of the fuel cell, and pure oxygen is introduced into the cathode side, and then the polarization curve of the fuel cell is measured, such as Figure 1 As shown in the figure (solid points represent the curve of voltage versus current density, and hollow points represent the curve of power density versus current density), the peak power density of the film electrode prepared based on the electrode plated with RuCoMn catalyst can reach 1.25 W cm at the back pressure of 0 MPa, 0.1 MPa and 0.2 MPa (compared to the standard atmospheric pressure). -2 、2.06W·cm -2 and 2.46 W·cm -2 When testing the anti-reverse polarity, humidified nitrogen is introduced into the anode and air is introduced into the cathode to simulate the hydrogen-deficient environment of the anode. Figure 2 As shown, the electrode prepared based on the plated RuCoMn catalyst can resist the reverse polarity for more than 120 hours, while the commercial PtC has an anti-reverse polarity time of only 5 minutes.
[0042] Example 2
[0043] An electroplating solution for preparing an electrode with high anti-reverse polarity performance comprises the following raw materials: 200 mg of a noble metal precursor RuCl3, 65 mg of a non-noble metal precursor CoSO4, 93 mg of a non-noble metal particle precursor TiCl4, 2 g of an additive K2SO4, and 100 ml of deionized water.
[0044] A method for preparing an electrode with high anti-reverse polarity performance for a fuel cell comprises the following steps:
[0045] (1) Pour 100 ml of deionized water into a beaker, then weigh 200 mg of RuCl3, 65 mg of CoSO4, 93 mg of TiCl4 and 2 g of K2SO4 into the beaker and stir well to form a uniform solution.
[0046] (2) Cut a 2 cm × 2 cm piece of carbon paper and place it in a beaker containing ethanol solution and ultrasonicate for 30 min.
[0047] (3) Carbon paper was used as the cathode and the anode was a cobalt rod with a length of 8 cm and a diameter of 2 mm.
[0048] (4) Then a gradient voltage is applied across the electrodes, ① at 2 mA cm -2 ② At 6 mA·cm -2 ③ At 10 mA·cm -2 ④ At 6 mA·cm -2 ⑤ At 2 mA·cm -2 current density and run for 1 min, then cycle 2 times according to ①②③④⑤.
[0049] (5) Calcine the plated electrode carbon paper at 350°C in a hydrogen atmosphere for 1 h.
[0050] (6) Then apply a gradient voltage to both ends of the electrode obtained in step 5, ① at 6 mA cm -2 ② At 10 mA·cm -2 ③ At 15 mA·cm -2 ④ At 10 mA·cm -2 ⑤ At 6 mA·cm -2 current density and run for 2min, then cycle 6 times according to ①②③④⑤.
[0051] (7) The plated electrode carbon paper was calcined at 350 °C in a nitrogen atmosphere for 2 h.
[0052] Test method for fuel cell anti-reverse polarity: Weigh 100 mg of Pt / C to make a slurry as the cathode and anode catalyst of the fuel cell, and the anode equivalent is 0.1 mg / cm 2 , cathode equivalent is 0.3mg / cm 2 , and then the anode is an electrode plated with RuCoTi catalyst, and the cathode is carbon paper without catalyst coating, and then a membrane electrode is prepared.
[0053] When testing the performance, pure hydrogen is introduced into the anode side of the fuel cell, pure oxygen is introduced into the cathode side, and then the polarization curve of the fuel cell is measured. When testing the anti-reverse polarity, humidified nitrogen is introduced into the anode and air is introduced into the cathode to simulate the hydrogen-deficient environment of the anode.
[0054] Example 3
[0055] The invention discloses an electroplating solution for preparing an electrode with high anti-reverse polarity performance, comprising the following raw materials: 200 mg of a noble metal precursor RuCl3, 65 mg of a non-noble metal precursor CoSO4, 117 mg of a non-noble metal particle precursor MoCl4, 2 g of an additive K2SO4, and 100 ml of deionized water.
[0056] A method for preparing an electrode with high anti-reverse polarity performance for a fuel cell comprises the following steps:
[0057] (1) Pour 100 ml of deionized water into a beaker, then weigh 200 mg of RuCl3, 65 mg of CoSO4, 117 mg of MoCl4 and 2 g of K2SO4 into the beaker and stir well to form a uniform solution.
[0058] (2) Cut a 2 cm × 2 cm piece of carbon paper and place it in a beaker containing ethanol solution and ultrasonicate for 30 min.
[0059] (3) Carbon paper was used as the cathode and the anode was a cobalt rod with a length of 8 cm and a diameter of 2 mm.
[0060] (4) Then a gradient voltage is applied across the electrodes, ① at 2 mA cm -2 ② At 6 mA·cm -2 ③ At 10 mA·cm -2 ④ At 6 mA·cm -2 ⑤ At 2 mA·cm -2 current density and run for 1 min, then cycle 2 times according to ①②③④⑤.
[0061] (5) Calcine the plated electrode carbon paper at 350°C in a hydrogen atmosphere for 1 h.
[0062] (6) Then apply a gradient voltage to both ends of the electrode obtained in step 5, ① at 6 mA cm -2 ② At 10 mA·cm -2 ③ At 15 mA·cm -2 ④ At 10 mA·cm -2⑤ At 6 mA·cm -2 current density and run for 2min, then cycle 6 times according to ①②③④⑤.
[0063] (7) The plated electrode carbon paper was calcined at 350 °C in a nitrogen atmosphere for 2 h.
[0064] Test method for fuel cell anti-reverse polarity: Weigh 100 mg of Pt / C to make a slurry as the cathode and anode catalyst of the fuel cell, and the anode equivalent is 0.1 mg / cm 2 , cathode equivalent is 0.3mg / cm 2 , and then the anode is an electrode plated with RuCoMo catalyst, and the cathode is carbon paper without catalyst coating, and then a membrane electrode is prepared.
[0065] When testing the performance, pure hydrogen is introduced into the anode side of the fuel cell, pure oxygen is introduced into the cathode side, and then the polarization curve of the fuel cell is measured. When testing the anti-reverse polarity, humidified nitrogen is introduced into the anode and air is introduced into the cathode to simulate the hydrogen-deficient environment of the anode.
[0066] Example 4
[0067] An electroplating solution for preparing an electrode with high anti-reverse polarity performance comprises the following raw materials: 200 mg of a noble metal precursor RuCl3, 65 mg of a non-noble metal precursor CoSO4, 133 mg of a non-noble metal particle precursor NbCl5, 2 g of an additive K2SO4, and 100 ml of deionized water.
[0068] A method for preparing an electrode with high anti-reverse polarity performance for a fuel cell comprises the following steps:
[0069] (1) Pour 100 ml of deionized water into a beaker, then weigh 200 mg of RuCl3, 65 mg of CoSO4, 133 mg of NbCl5 and 2 g of K2SO4 into the beaker and stir well to form a uniform solution.
[0070] (2) Cut a 2 cm × 2 cm piece of carbon paper and place it in a beaker containing ethanol solution and ultrasonicate for 30 min.
[0071] (3) Carbon paper was used as the cathode and the anode was a cobalt rod with a length of 8 cm and a diameter of 2 mm.
[0072] (4) Then a gradient voltage is applied across the electrodes, ① at 2 mA cm -2 ② At 6 mA·cm -2 ③ At 10 mA·cm -2 ④ At 6 mA·cm -2⑤ At 2 mA·cm -2 current density and run for 1 min, then cycle 2 times according to ①②③④⑤.
[0073] (5) Calcine the plated electrode carbon paper at 350°C in a hydrogen atmosphere for 1 h.
[0074] (6) Then apply a gradient voltage to both ends of the electrode obtained in step 5, ① at 6 mA cm -2 ② At 10 mA·cm -2 ③ At 15 mA·cm -2 ④ At 10 mA·cm -2 ⑤ At 6 mA·cm -2 current density and run for 2min, then cycle 6 times according to ①②③④⑤.
[0075] (7) The plated electrode carbon paper was calcined at 350 °C in a nitrogen atmosphere for 2 h.
[0076] Test method for fuel cell anti-reverse polarity: Weigh 100 mg of Pt / C to make a slurry as the cathode and anode catalyst of the fuel cell, and the anode equivalent is 0.1 mg / cm 2 , cathode equivalent is 0.3mg / cm 2 Then the anode is an electrode plated with RuCoNb catalyst, and the cathode is carbon paper without catalyst coating, and then a membrane electrode is prepared.
[0077] When testing the performance, pure hydrogen is introduced into the anode side of the fuel cell, pure oxygen is introduced into the cathode side, and then the polarization curve of the fuel cell is measured. When testing the anti-reverse polarity, humidified nitrogen is introduced into the anode and air is introduced into the cathode to simulate the hydrogen-deficient environment of the anode.
[0078] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the present invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.
Claims
1. A method for preparing an electrode with high anti-reverse polarity performance for a fuel cell, characterized in that: The following steps are involved: (1) stirring deionized water, non-precious metal precursor, precious metal precursor and additive to form a uniform solution; (2) placing the cathode electrode in ethanol for ultrasonic treatment; (3) Metal rods or metal sheets as anodes; (4) Apply a gradient voltage across the electrodes for 1 to 3 cycles; (5) calcining the plated cathode electrode in a reducing atmosphere; (6) then applying a gradient voltage to both ends of the electrode obtained in step (5) for 2 to 6 cycles; (7) calcining the plated cathode electrode in a stable atmosphere to obtain the electrode with high anti-reverse polarity performance for the fuel cell.
2. The method for preparing an electrode with high anti-reverse polarity performance for a fuel cell according to claim 1, characterized in that: In step (1), the weight proportions of the raw materials are as follows: 1 to 200 parts of deionized water, 0.1 to 25 parts of non-precious metal precursor, 0.1 to 50 parts of precious metal precursor, and 1 to 200 parts of additives.
3. The method for preparing an electrode with high anti-reverse polarity performance for a fuel cell according to claim 1, characterized in that: In step (1), the non-precious metal precursor is one or more of CoSO4, MnSO4, NbCl5, MoCl4 or TiCl4, the precious metal precursor is RuCl3 or H2IrCl6, and the additive is K2SO4 or Na2SO4.
4. The method for preparing an electrode with high anti-reverse polarity performance for a fuel cell according to claim 1, characterized in that: In step (2), the cathode electrode is one of carbon paper, titanium felt, nickel felt or titanium mesh; the size of the cathode electrode is 2×2 to 5×5 cm 2 , the ultrasonic time is 30 to 60 minutes.
5. The method for preparing an electrode with high anti-reverse polarity performance for a fuel cell according to claim 1, characterized in that: In step (3), the metal rod is one of a cobalt rod, an iron rod, a nickel rod, and a copper rod, and the metal sheet is one of a cobalt sheet, an iron sheet, a nickel sheet, and a copper sheet.
6. The method for preparing an electrode with high anti-reverse polarity performance for a fuel cell according to claim 1, characterized in that: In step (4), the gradient voltage is set as follows: 1-3 mA·cm -2 The current density was 5-7 mA·cm -2 The current density is 10-12 mA·cm -2 The current density was 5-7 mA·cm -2 The current density is 1-3 mA·cm -2 The current density is set and run for 1 to 3 minutes.
7. The method for preparing an electrode with high anti-reverse polarity performance for a fuel cell according to claim 1, characterized in that: In step (5), the reducing atmosphere is one of H2, CO or N2\H2 mixed gas; the calcination temperature is 250-500°C and the calcination time is 1-3h.
8. The method for preparing an electrode with high anti-reverse polarity performance for a fuel cell according to claim 1, characterized in that: In step (6), the gradient voltage is set as follows: 4-6 mA·cm -2 The current density is 8-10 mA·cm -2 The current density is 14-16 mA·cm -2 The current density is 8-10 mA·cm -2 The current density is 4-6 mA·cm -2 The current density is set and run for 1 to 5 minutes.
9. The method for preparing an electrode with high anti-reverse polarity performance for a fuel cell according to claim 1, characterized in that: In step (7), the stabilizing atmosphere is one of N2, Ar or N2 / Ar mixed gas; the calcination temperature is 250-500°C, and the calcination time is 1-3h.
10. An electrode with high anti-reverse polarity performance for a fuel cell prepared by the method for preparing an electrode with high anti-reverse polarity performance for a fuel cell according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparing method of catalyst electrode of fuel cell
CN101290989A
Preparation process of molybdenum / palladium / silver laminar metal matrix composite
CN103668368A
Preparation method of nitrogen-doped carbon paper oxygen reduction reaction catalyst
CN112002912A
Metal ruthenium-based electrode and preparation method and application thereof
CN113603191A
Anti-reverse-pole catalyst for fuel cell and preparation method of anti-reverse-pole catalyst
CN113707897A